Neoropricing dan Etika Bisnis Islam - M. Sulaeman Jajuli (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2020)
ABSTRACTNeuropricing is the brain physiologically which is influenced by advertising and is a marketing strategy in determining the form of price, but basically neuropricing is oriented to the commercial price alone. For Muslim economists, Muslim business actors and Muslim consumers need to consider aspects of sharia law when interacting in doing business, especially when studying in the study of fikh muamalat, even though the neuropricing used is only a strategy in delivering an advertisement so that consumers are more interested in the goods being marketed. Is this part of brain manipulation, even though in practice it is a price game (ghabn fahisy) or in modern dictionaries it is called a psychological price whose legal provisions are not clear? That needs to be a major concern for Muslims in particular, so that with this study it becomes clear the boundaries of Islamic ethics and norms on neuromarketing practices in marketing strategies.Keywords : Ethics, Business, and Neuropricing.